Improving surface stability on natural turfgrass athletic fields - Serensits, T. J.; McNitt, A. S.; Petrunak, M. D. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2011)
Regardless of the intensity of use, athletic fields are expected to provide a safe stable playing surface. As field use increases, wear caused by foot traffic can result in a loss of both turfgrass coverage and surface stability, increasing the risk of athlete injury. As surface stability is reduced, susceptibility to divoting is increased. The effect of synthetic soil reinforcements on the divot resistance of perennial ryegrass (Lolium perenne L.) under various simulated traffic levels was investigated. Soil-reinforcing materials improved divot resistance most under high traffic. Because the plant growth regulator trinexapac-ethyl (TE) has been shown to increase tiller density and rooting, its effect on divot resistance was evaluated on turfgrass grown on a sand root zone. TE (0.17 kg active ingredient/ha) was applied to Kentucky bluegrass (Poa pratensis L.) at 28 day intervals from either May to July or May to October. Plots were subjected to various levels of simulated traffic in the fall. Compared with the control, the application of TE from May to July resulted in the highest divot resistance. Various methods such as the inclusion of soil reinforcements and plant growth regulator applications can be used to decrease susceptibility to divoting.